PERTIMBANGAN YURIDIS HAKIM PADA PELAKU PENGIDAP GANGGUAN EKSIBISIONISME (Faculty of Law, University of Palembang, 2023)
Exhibitionism is included as a criminal act. However, in psychology, several cases of exhibitionism when carrying out these actions are caused by the sexual preferences of the sufferer. This, of course, is closely related to the reasons for forgiveness set forth in Article 44 of the Criminal Code. Therefore, this article will examine how the judge's juridical considerations in decision Number 40/Pid.Sus/2021/PN SKw sentence a defendant who experienced exhibitionism